1991
DOI: 10.1084/jem.174.1.151
|View full text |Cite
|
Sign up to set email alerts
|

The mouse antibody response to infection with Cryptococcus neoformans: VH and VL usage in polysaccharide binding antibodies.

Abstract: SummaryCryptocotcus neoformans is a ubiquitous fungus that can cause serious infections in humans. The fungus has a polysaccharide (C. neoformans capsular polysaccharide ; CNPS) capsule that contributes to its pathogenicity and can elicit an antibody response . Nevertheless, only 4 of 60 BALB/c mice chronically infected with C. neoformans had a detectable increase in serum anti-CNPS. The sera of three responder mice contained both IgM and IgG anti-CNPS antibody, and the titers of A and K anti-CNPS antibody wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 52 publications
(56 reference statements)
3
104
0
Order By: Relevance
“…Restriction of Ig gene usages in antigen-specific B cells have been reported in both animal and human studies of antibody responses towards a variety of antigens, ranging from hapten, carbohydrate, viral protein, Rhesus D antigens, to other self proteins (Berek and Milstein, 1987;Casadevall and Scharff, 1991;Minnerath et al, 1995;Perera et al, 2000a;Perera et al, 2000b;Zhang et al, 2006), while others reported diverse antibody responses to confined regions of foreign proteins or homologs of self proteins (Andria et al, 1990;Caton et al, 1991;Kalinke et al, 1996). We previously showed that antibody gene usages of rotavirus (RV)-specific B cells differed from that of randomly selected B cells, with a distinct bias in the usage of gene segments in the V H 1 and V H 4 families.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of Ig gene usages in antigen-specific B cells have been reported in both animal and human studies of antibody responses towards a variety of antigens, ranging from hapten, carbohydrate, viral protein, Rhesus D antigens, to other self proteins (Berek and Milstein, 1987;Casadevall and Scharff, 1991;Minnerath et al, 1995;Perera et al, 2000a;Perera et al, 2000b;Zhang et al, 2006), while others reported diverse antibody responses to confined regions of foreign proteins or homologs of self proteins (Andria et al, 1990;Caton et al, 1991;Kalinke et al, 1996). We previously showed that antibody gene usages of rotavirus (RV)-specific B cells differed from that of randomly selected B cells, with a distinct bias in the usage of gene segments in the V H 1 and V H 4 families.…”
Section: Discussionmentioning
confidence: 99%
“…mAbs 3E5 and 4H3 both bind GXM, but each differ in specificity and V region usage (11). mAb 3E5 IgG3 (11,12), which was generated from a B cell isolated from a mouse immunized with GXM-tetanus toxoid, uses V H 7183 and V K 5.1 gene elements and binds to an epitope found in all serotypes of GXM (13). The murine Ab response to GXM is highly restricted because the majority of mAbs to GXM that were isolated either from infected mice or from mice immunized with GXM-tetanus toxoid (11) are encoded by V H 7183.…”
mentioning
confidence: 99%
“…Given the finding that the C region can affect V region fine specificity and Id might have major implications for several current immunological concepts, and that none of the observations suggesting this view are conclusive, we have investigated this problem further by comparing the fine specificity of two families of murine IgG switch variants, 3E5 and 4H3, that bind to C. neoformans GXM polysaccharide. mAbs 3E5 and 4H3 both bind GXM, but each differ in specificity and V region usage (11). mAb 3E5 IgG3 (11,12), which was generated from a B cell isolated from a mouse immunized with GXM-tetanus toxoid, uses V H 7183 and V K 5.1 gene elements and binds to an epitope found in all serotypes of GXM (13).…”
mentioning
confidence: 99%
“…mAb 2H1 and 18B7 are IgG1 (6), whereas mAbs 12A1, 13F1, and 21D2 are IgMs (6,16,18). The isotypes of other Abs used in this study are listed within Results.…”
Section: Monoclonal Absmentioning
confidence: 99%